2006
DOI: 10.1007/s10712-006-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

2-D Versus 3-D Magnetotelluric Data Interpretation

Abstract: Abstract. In recent years, the number of publications dealing with the mathematical and physical 3-D aspects of the magnetotelluric method has increased drastically. However, field experiments on a grid are often impractical and surveys are frequently restricted to single or widely separated profiles. So, in many cases we find ourselves with the following question: is the applicability of the 2-D hypothesis valid to extract geoelectric and geological information from real 3-D environments? The aim of this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 100 publications
0
33
0
Order By: Relevance
“…The tipper is included where available, which is most of the land stations. Caution over use of the TE mode arises over concerns of the impacts of potential 3D structure on a 2D inversion: TM mode data are less sensitive to finite strike effects (e.g., Wannamaker, 1999;Ledo, 2005). Inversions were run using the 2D inversion of Rodi and Mackie (2001) as implemented within the Winglink software package.…”
Section: Modelingmentioning
confidence: 99%
“…The tipper is included where available, which is most of the land stations. Caution over use of the TE mode arises over concerns of the impacts of potential 3D structure on a 2D inversion: TM mode data are less sensitive to finite strike effects (e.g., Wannamaker, 1999;Ledo, 2005). Inversions were run using the 2D inversion of Rodi and Mackie (2001) as implemented within the Winglink software package.…”
Section: Modelingmentioning
confidence: 99%
“…The result of this analysis shows that our data are mainly 3D. However, if a preferential direction can be determined, the 2D inversion of the impedance tensor determinant makes a reasonable approximation to 3D structures in many cases (Pedersen and Engels 2005;Ledo 2006), which is the case for this deltaic system. Based on the fluvio-deltaic facies distribution, transitional boundaries and main stratigraphical continuity tendencies, it can be observed that profiles PS1 and PS4 follow the actual river channel and its perpendicular direction, respectively, and therefore we have created 2D resistivity models using the determinant of the impedance tensor mode.…”
Section: Amt Methodsmentioning
confidence: 70%
“…5). This parameter is invariant under rotation and makes it suitable for qualitative interpretation (Vozoff 1972;Ledo 2006). Responses over 3D structures may show complex behaviour for individual impedancetensor elements, whereas much simpler and less distorted behavior of the determinant impedance usually can be well explained by 2D models (Pedersen and Engels 2005).…”
Section: Amt Methodsmentioning
confidence: 99%
“…2-D inversions are then performed to yield 2-D cross-sectional models for profile interpretation. The dangers of 2-D inversions being influenced by 3-D structures are demonstrated with synthetic data in Siripunvaraporn et al (2005b) and Ledo (2006) and with real data in Simpson and Bahr (2005) and Newman et al (2003). All studies indicate that if the data contains 3-D structures, 2-D inversion can mislead an interpretation.…”
Section: When Is 3-d Inversion Useful? (Advantages Of 3-d Inversion Omentioning
confidence: 89%